2020
DOI: 10.3390/catal10101149
|View full text |Cite
|
Sign up to set email alerts
|

Acid/Base-Treated Activated Carbon Catalysts for the Low-Temperature Endothermic Cracking of N-Dodecane with Applications in Hypersonic Vehicle Heat Management Systems

Abstract: Hypersonic aircrafts suffer from heat management problems caused by the air friction produced at high speeds. The supercritical catalytic cracking of fuel is endothermic and can be exploited to remove heat from the aircraft surfaces using specially designed heat management systems. Here, we report that an acid/base-treated activated carbon (AC) catalyst shows superior performance to the conventional ZSM-5 catalyst at 4 MPa and 450 °C. Further, under these conditions, coke formation is thermodynamically avoided… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…Although the acidity of nano-ZSM-5 and the associated properties promoted the dodecane conversion levels both in the presence and absence of steam, the concurrent flow of steam in the reaction affected the pore shape selectivity of the catalyst and altered the mechanism more toward the β-scission reaction 59 and achieved higher selectivity towards olefins. 58 However, in the absence of steam, the carbenium ions in ZSM-5(P) promoted higher C–C cracking through the β-scission mechanism and made more dry gas and ethylene products, especially at higher temperatures. On the other hand, dodecane cracking via ZSM-5(ST) in the absence of steam achieved low olefin selectivity and an increase in LPG products (propane and n -butane, and iso-butane), indicating that the zeolite pores inclined toward the hydrogenation reaction route of olefin to LPG.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the acidity of nano-ZSM-5 and the associated properties promoted the dodecane conversion levels both in the presence and absence of steam, the concurrent flow of steam in the reaction affected the pore shape selectivity of the catalyst and altered the mechanism more toward the β-scission reaction 59 and achieved higher selectivity towards olefins. 58 However, in the absence of steam, the carbenium ions in ZSM-5(P) promoted higher C–C cracking through the β-scission mechanism and made more dry gas and ethylene products, especially at higher temperatures. On the other hand, dodecane cracking via ZSM-5(ST) in the absence of steam achieved low olefin selectivity and an increase in LPG products (propane and n -butane, and iso-butane), indicating that the zeolite pores inclined toward the hydrogenation reaction route of olefin to LPG.…”
Section: Resultsmentioning
confidence: 99%
“…Through b-scission via the short-diffusion-length pores of nanoscale zeolite, the carbenium ions formed the essential primary cracking pathway toward promoting higher olen production. Typically, in the presence of steam, the monomolecular reaction is favoured, hindering the hydrogenation and alkylation of olens 58 and lowering the formation of LPG and C5+ byproducts due to the low activation energies. 11 In summary, steam-treated nanoscale ZSM-5 with the extraframework alumina species maintained high activity despite the decline in surface acidity.…”
Section: 32mentioning
confidence: 99%
“…33,34 In the catalytic cracking of polymers, both Lewis and Brønsted acid sites are important because they both attribute to the generation of carbenium ions. 35 We have found that the Lewis acidity of zeolites is important for the catalytic degradation of plastics. 36,37 So far, many efforts have been made to enhance the Lewis acidity of zeolites, and it has been reported that this can be achieved by doping metals ( e.g.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Hummer's method involves the use of sulfuric acid, potassium permanganate as an oxidant, water, and heating process [13]. Similarly, our previous studies have shown that large amounts of oxygen functional groups (OFGs) can be introduced onto activated charcoal via sequential NaOH and acid treatments, albeit through laborious and complex steps [14].…”
Section: Introductionmentioning
confidence: 99%